2019
DOI: 10.1021/acssuschemeng.9b05098
|View full text |Cite
|
Sign up to set email alerts
|

Highly Stable Na3Fe2(PO4)3@Hard Carbon Sodium-Ion Full Cell for Low-Cost Energy Storage

Abstract: Abundant flake-porous Na3Fe2(PO4)3 has been prepared via a simple spray drying method. As a cathode material in sodium-ion batteries (SIBs), the galvanostatic charge/discharge test results indicate that the initial reversible discharge specific capacity of the flake-porous Na3Fe2(PO4)3 electrode can reach to 100.8 mAh g–1 (about 93% of the theoretical capacity of 105 mAh g–1) under a current density of 10 mA g–1 (0.1 C) and the high rate capability at 500 mA g–1 (5 C) is up to 60 mAh g–1 after 1100 cycles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…Even the ultrahigh power density increase up to 23 and 30 kW kg −1 , the energy density of 58 and 38 Wh kg −1 are achieved. On the basis of a comprehensive literature study among the reported SIBs, [ 51–54 ] sodium‐ion capacitors (SICs), [ 55,56 ] lithium‐ion capacitors (LICs), [ 49,57 ] and electric double‐layer capacitors (EDLCs), [ 49 ] to the best of our knowledge, the MCMB|Na + ‐diglyme|NVP SIB realizes the challenge of achieving a high energy density at an ultrahigh power density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the ultrahigh power density increase up to 23 and 30 kW kg −1 , the energy density of 58 and 38 Wh kg −1 are achieved. On the basis of a comprehensive literature study among the reported SIBs, [ 51–54 ] sodium‐ion capacitors (SICs), [ 55,56 ] lithium‐ion capacitors (LICs), [ 49,57 ] and electric double‐layer capacitors (EDLCs), [ 49 ] to the best of our knowledge, the MCMB|Na + ‐diglyme|NVP SIB realizes the challenge of achieving a high energy density at an ultrahigh power density.…”
Section: Resultsmentioning
confidence: 99%
“…c) Ragone plots of the full‐cell SIB. Comparison of the energy density versus power density plots between the MCMB||NVP@C@CNTs and the other reported SIBs, [ 51–54 ] SICs, [ 55,56 ] LICs, [ 49,57 ] and EDLCs. [ 49 ] d) Long‐term cycling performance of the full‐cell SIB at 5 A g −1 .…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, we have compared the electrochemical outputs of MSVP-based cathodes with those of well-renowned NASICON type cathodes in terms of energy density, cycling stability, and rate capability (Table 3). It should be noted that the energy density, cycling stability, and rate capability of MSVP-based cathodes are comparable to those of standard NASCION type cathodes including Na 3 V 2 (PO 4 ) 3 , 82 Na 3 V 2 (PO 4 ) 2 F 3 , 83 Na 3 Fe 2 (PO 4 ) 3 , 84 Na 3 MnTi(PO 4 ) 3 , 45 and Na 2 TiV(PO 4 ) 3 , 85 validating that MSVP-based cathodes are not only economical but also electrochemically competitive. In a short span of time, multiple synthetic techniques, including solid-state, sol–gel, pyrosynthesis, spray–drying, and radical polymerization techniques, have been used for the fabrication of MSVP-based cathodes with good electrochemical properties.…”
Section: Critical Challenges Surrounding Msvp-based Cathodes and Possible Strategies For Overcoming Themmentioning
confidence: 72%
“…Besides, their corresponding galvanostatic discharge curves at various rates present similar voltage plateau of ≈1.2 V with inconspicuous polarization (inset in Figure 5c), further confirming its superior LT C‐rate ability. As illustrated in Figure 5d, the LT rate capability of our NTP/CF||NVP/CF cell is certainly brilliant, which outperforms most of the previous full cells such as NaV 1.25 Ti 0.75 O 4 (or hard carbon)||Na 0.8 Ni 0.4 Ti 0.6 O 2 , [ 18 ] hard carbon||Na 3 Fe 2 (PO 4 ) 3 , [ 19 ] and NTP@C||Ni(OH) 2 . [ 20 ] More remarkably, our designed NTP/CF||NVP/CF with enhanced Na + diffusivity displays an exceptional long‐term cyclability under low temperature (−20 °C) and high rate (>10 C), e.g., stabilizing at about 44 mA h g −1 (10 C, k = 73%) and 36 mA h g −1 (20 C, k = 60%) over 1000 cycles (Figure 5e), which brings an important step forward in the development of LT SIBs.…”
Section: Resultsmentioning
confidence: 92%